Nonlinear modeling of MDOF structures equipped with viscoelastic dampers with strain, temperature and frequency-dependent properties. (1st August 2018) - Ghaemmaghami, Amir Reza; Kwon, Oh-Sung
Highlights: Propose a method by which the nonlinear time-history response of an inelastic hysteretic MDOF system coupled with a frequency, strain and temperature dependent VE damper is assessed. Improve recursive-parameter models in order to incorporate strain- and temperature-dependent properties of VE dampers into the numerical model. Verify the propose model against analytical and experimental results. Apply the proposed method to a practical engineering case including nonlinear time-history analysis of a 20-story tall building subjected to seismic ground motions. Compared the methods with the classical Kelvin-Voigt method which is widely employed in the practice in order to assess the accuracy of the practical model. Abstract: The main objective of this paper is to propose a numerical algorithm for modeling the nonlinear time-history seismic response of MDOF structures with frequency-, strain- and temperature-dependent viscoelastic (VE) dampers. An extended recursive parameter model based on Nakamura's method is established in order to simulate the frequency-, strain- and temperature-dependent properties of VE dampers in the time domain. The numerical stability of the extended model combined with a time-stepping method is studied and the model is verified against the exact solution for linear response as well as the experimental measurements for nonlinear response. A full-fledged nonlinear time-history analysis of a practical engineering problem is carried out and the results are compared with those calculated by traditional Kelvin-Voigt model which is commonly used in the practice as well as fractional derivative (FD) method. The advantages and robustness of the proposed method is then fully discussed.